(-7) - 2 =
8 + 2 =
(-9) - (-6) =
10 + 4 =
(-4) - (-2) =
6 + 10 =
5 - 6 =
(-8) + (-5) =
6 - (-6) =
3 - (-6) =
(-4) + (-8) =
(-3) - (-5) =
(-2) - 8 =
(-6) - 10 =
(-10) + (-7) =
7 + 10 =
8 + 10 =
(-1) + 6 =
8 - (-1) =
2 - (-1) =
9 + (-1) =
(-4) + 5 =
(-8) - 1 =
4 + (-7) =
1 - 10 =
(-10) + (-8) =
(-6) - 1 =
7 - 2 =
(-9) + 4 =
(-9) - (-4) =
Respuestas
Respuesta dada por:
14
Respuesta:
(-7)-2=-9
8+2=10
(-9)-(-6)=-3
10+4=14
(-4)-(-2)=-2
6+10=16
Explicación paso a paso:
rojasyasi21:
gracias
(-8) + (-5) =-13
6 - (-6) =12
3 - (-6) =9
(-4) + (-8) =-8
(-3) - (-5) =-11
(-2) - 8 =-10
(-6) - 10 =-16
(-10) + (-7) =-17
7 + 10 =17
8 + 10 =18
(-1) + 6 =5
8 - (-1) =9
2 - (-1) =3
9 + (-1) =8
(-4) + 5 =1
(-8) - 1 =-9
4 + (-7) =3
1 - 10 =9
(-10) + (-8) =-18
(-6) - 1 =-7
7 - 2 =5
(-9) + 4 =-5
(-9) - (-4) =-5
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años